PENUNDAAN PEMBAGIAN HARTAWARIS (Studi Kasus di Dusun Gebangmalang Desa Bandung Kabupaten Jombang) - Faruq, Ahmad (Irtifaq, 2024)
2023, Bayu Agung Prasetya: The purpose of this article is to provide information on the prevalence of human trafficking in Gebangmalang Hamlet, Bandung Village, Jombang Regency and theprevalence of human trafficking within the Islamic religion in Gebangmalang Hamlet, Bandung Village, Jombang Regency.One of the methods used in this study is a qualitative method that uses data collection as its mainmethod. The information provided in this article is for Gebanghmalang mobs and mobs.Information analysis using inductive and descriptive methods.This means that the side of the heart that is being used is the same as the side of the heart that is being used; However, there are several factors that need to be considered to identify identified parties. Therefore, the inheritance that has not been divided must be immediately distributed to the heirs who are entitled, for fear that there will be misuse of the inheritance so that it takes the rights of others either intentionally or unintentionally. In addition to Islamic inheritance law, there is also ijbari which can be found in heirs if they don't like it and are out of reach. Before distributing theinheritance to the heirs who are entitled, the inheritance must meet the needs of the deceased from bathing, shrouding, burial, payment of debts, zakat to wills. After that,then what must be used by those who have an interest, and what must be used by those who have an interest in accordance with the teachings of the Qur'an and the Sunnah of the Prophet and their Impact: It is illegal when the property is sold by one of the heirs without the consent of the heirs.